The effectiveness of intrapartum cardiotocography with fetal outcome-a hospital-based study - Sarker, Anima; Anjuman Ara; Mosammat Shahina Begum; Juthi Bhowmik; Hafija Akter; Shanta Fahmida Haque; Shah Jasmine Basir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The determination of the fetal condition during labour is important to minimize fetal mortality, morbidity and neurological sequelae of fetal hypoxia. The study aims to evaluate the effectiveness of intrapartum cardiotocography (CTG) in detecting fetal outcomes. Methods: This cross-sectional observational study was conducted at the department of obstetrics and gynecology in the centre for women and child health (CWCH), Ashulia, Dhaka from November 2020 to August 2022. The study was carried out with a total of 63 pregnant women (n=63) who had delivered their child either by lower uterine caesarian section (LUCS) or normal vaginal delivery (NVD) during the study period. Result: Among the participants, almost half participants (47.6%) were aged between 25-29 years. Intrapartum CTG was reactive in around half (54%) of the participants, while non-reactive in 46% of the participants. During the study period, intrapartum CTG was reactive in 34 patients. Of them, only 19 patients had an NVD, while 15 patients despite normal intrapartum CTG also underwent LUCS due to various reasons such as having meconium-stained liquor or slightly stained liquor, non-progressing labour or prolonged labour, premature rupture of the membrane (PROM), fear of NVD etc. During the study period, all twenty-nine patients having intrapartum non-reactive CTG underwent LUCS. During the study period, intrapartum CTG was non-reactive in 29 cases. However, after delivery, the baby’s APGAR score was ≥7 for the 20 neonates of those 29 non-reactive CTG cases. On the other hand, intrapartum CTG was reactive in 34 of the participants. Among them, 3 neonates were delivered through NVD. However, meconium-stained liquor was found and the baby’s APGAR score was <7, which required NICU admission. In total, thirteen neonates (13, 20.6%) had required admission to the neonatal intensive care unit (NICU). Conclusions: CTG is one of the reliable methods of monitoring the fetus. Non-reactive CTG record with a high probability indicates the likelihood of the presence of perinatal asphyxia. Instant and adequate decisions regarding obstetric intervention and optimal procedures should be taken if fetal distress is suspected.